A New Look at Molecular and Electronic Structure of Homoleptic Diiron(II, II) Complexes with N, N‐Bidentate Ligands: Combined Experimental and Theoretical Study. Issue 40 (2nd June 2022) - Korona, Krzesimir; Terlecki, Michał; Justyniak, Iwona; Magott, Michał; Żukrowski, Jan; Kornowicz, Arkadiusz; Pinkowicz, Dawid; Kubas, Adam; Lewiński, Janusz
Abstract: Paddlewheel‐type binuclear complexes featuring metal−metal bonding have been the subject of widespread interest due to fundamental concern in their electronic structures and potential applications. Here, we explore the molecular and electronic structures of diiron(II, II) complexes with N, N' ‐diarylformamidinate ligands. While a paddlewheel‐type diiron(II, II) complex with N, N' ‐diphenylformamidinate ligands (DPhF) exhibits the centrosymmetric [Fe2 ( μ ‐DPhF)4 ] structure, a minor alteration in the ligand system, i. e., switching from phenyl to p‐ tolyl N ‐substituted formamidinate ligand (DTolF), resulted in the isolation of an unprecedented non‐centrosymmetric [Fe( μ ‐DTolF)3 Fe( κ 2 ‐DTolF)] complex. Both complexes were characterized using single‐crystal X‐ray diffraction, magnetic measurements, 57 Fe Mössbauer spectroscopy, and cyclic voltammetry along with high‐level ab‐initio calculations. The results provide a new view on a range of factors controlling the ground‐state electronic configuration and structural diversity of homoleptic diiron(II, II) complexes. Model calculations determined that the Mayer bond orders for Fe−Fe interactions are significantly lower than 1 and equal to 0.15 and 0.28 for [Fe2 ( μ ‐DPhF)4 ] and [Fe( μ ‐DTolF)3 Fe( κ 2 ‐DTolF)], respectively. Abstract : The new factors governing the molecular and electronic structures of Fe−Fe bonded diiron(II, II) complexes were revealed based on comprehensive experimental characterization along with high‐level ab‐intio calculations. We present the unprecedented non‐centrosymmetric complex [Fe( μ ‐DTolF)3 Fe( κ 2 ‐DTolF)], and the new electronic configuration of paddlewheel‐type compound [Fe2 ( μ ‐DPhF)4 ].